Pemanfaatan Digital Marketing Untuk Meningkatkan Penjualan UMKM Taman Kakao Cokelat Slanden Banjaroyo dan Bas And Reng - Nurkhasanah, Septhia Fadhilla; Ratri Paramitalaksmi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Community service activities are carried out in two locations of Micro, Small and Medium Enterprises (MSMEs), namely Slanden Banjaroyo Chocolate Cocoa Park and Bas and Reng Wonosobo Buffet. This activity aims to examine the use of digital marketing to increase sales. In the era of digitalization, Micro, Small and Medium Enterprises (MSMEs) must adapt to changes in consumer behavior who are more likely to use digital platforms. In reality, MSME actors focus more on business income, but less on the use of digital marketing in expanding public reach. Chocolate Cocoa Park and Bas and Reng Buffet face obstacles in product marketing and the lack of product brand identity. In this community service activity, the author supports MSME actors to increase promotional activities through social media and the creation of logos and brochures on the Canva application. The results achieved after this activity was carried out was an increase in the understanding of business actors in applying digital media to market products and business actors already have a product brand identity.